The Title of the Growth of New Dynasties in Spain Maghrib and Iran - Suci Kirani Adhistia; Ellya Roza; Perisi Nopel (Education Achievement: Journal of Science and Research, 2024)
This research aims to examine the birth and development of new dynasties in the regions of the Spanish Maghrib and Iran after the collapse of major powers such as the Umayyad Caliphate in Spain and the Abbasid Caliphate in Iran. Employing a literature research approach, this study traces the background of the emergence, expansion processes, consolidation of power, as well as the contributions of these dynasties to the intellectual and cultural development in the regions they ruled. In the Spanish Maghrib, the Almoravid and Almohad Dynasties emerged as new powers after the fall of the Umayyad Caliphate. Both dynasties succeeded in uniting the regions of Spain and the Maghrib, albeit with different methods and ideologies. Meanwhile, in Iran, the Ilkhanid, Jalayirid, Timurid, and Safavid Dynasties rose after the collapse of the Abbasid Caliphate, each exerting significant influence and contributions to the political, cultural, artistic, and scientific development. The research findings indicate that the birth and development of these new dynasties not only brought about political changes but also contributed significantly to intellectual and cultural advancements in both regions. The periods under their rule are known as golden ages in the fields of art, architecture, literature, mathematics, astronomy, philosophy, and other sciences. These dynasties fostered the exchange of ideas among various ethnic and religious groups and created a conducive environment for the growth of knowledge and creativity. Overall, this study highlights the importance of the new dynasties in the dynamics of history and civilization, as well as their contributions in shaping new political landscapes and catalyzing the growth of rich knowledge, art, and culture.